Analyzing Role Playing Game and its Roles and Concepts Based on Collective Subject Discourse - Born, Miriam B.; Mota, Fernanda P.; de Aguiar, Marilton S.; Adamatti, Diana F. (Proceedings - Frontiers in Education Conference, 2023)
In the context of Environmental Education, games help understand a particular theme and allow the observation of the approach from a player's perspective. This study presents an analysis of the use of feedback in RPGs (Role-Playing Games) and the importance of carefully analyzing the concepts being used. Furthermore, we observe the difficulty of individuals in understanding their roles in the RPG in the water resources context. The main contribution of this work is an empirical and qualitative study of the motivation of individuals. As a result, we present the individual's speech through a semistructured interview based on the Collective Subject Discourse (CSD) technique.